Self-regulated Learning as a Mediator between Authoritative Parenting and Academic Achivement of Junior high School Students - Husnaini, Husnaini; Izzaty, Rita Eka (Universitas Muhammadiyah Yogyakarta, 2024)
This research begins with a situation that shows the low academic achievement of junior high school students. Self-regulated learning and authoritative parenting are supporting factors that produce students with good academic achievement. Therefore, this research aims to show the influence of self-regulated learning as a mediator between authoritative parenting and learning achievement in junior high school students in Depok District. This research approach was quantitative research using survey methods. This research was conducted in Depok District, Sleman Regency, with a sample of 303 students. Data collection techniques used cluster random sampling, with research instruments on the scales of authoritative parenting and self-regulated learning. The validity test used total score results (r), and the reliability test used Cronbach's Alpha, with an authoritative parenting style scale value of 0.862 and a self-regulated learning scale of 0.879. In addition, data analysis techniques were carried out using regression with PROCESS v4 for SPSS by Andrew F. Hayes. The research results show that self-regulated learning acts as a mediator between authoritative parenting and learning achievement. In this research, path c had a higher coefficient of 0.4181, and path c' was lower at 0.2501. Based on both, the regression coefficient c' decreased, proving the existence of partial mediation. It can be concluded that there is a partial mediation effect of self-regulated learning from authoritative parenting on learning achievement.